What Kind of Wellbeing Does He/She Want? Educational Possibilities for Children of New Immigrants From the Perspective of Agency - Teng Huang (National Taipei University of Education, 2022)
According to economists, we should think beyond the objective well-being indicators and pay more attention to the subjective well-being, agency, and capability of immigrants as the basis of immigration policy. However, few studies on the children of new immigrants in Taiwan have been conducted from the perspective of subjective well-being and agency. Since the concept of agency is still controversial, this study further considers the current research findings based on Giddens' theory of agency and explores possible directions for future study. It was found that current studies have focused on how children of new immigrants adapt to mainstream society rather than on developing their agency. This paper proposes two concrete directions for future studies through further investigation. First is to understand, at the micro level, the problems of the social position of the new immigrant children through their embodied experience and feelings to raise their conscious reflection and achieve their subjective well-being. Second is to understand, at the meso level, the interactions of new immigrant children with specific community members in communities of practice, so as to understand their constraints and the agentic strategies they utilize, which will serve as an important reference for future educational policies and practices.